Using Visual Histories to Reconstruct the Mental Context of Suspended Activities. (2nd November 2017) - Rule, Adam; Tabard, Aurélien; Hollan, Jim
Abstract : Resuming suspended activities is fundamental to knowledge work. As activities grow in complexity or fade from memory, they become increasingly difficult to cognitively resume. Motivated by the efficiency of images for cueing autobiographical memory, we conducted 2 studies of how visual histories of computer-mediated activity might aid users in restoring the mental context of suspended activities. In the first exploratory study we demonstrate that users provided a visual history consisting of small thumbnail images of their desktop can reconstruct detailed mental contexts of earlier computer work. In the second observational study we examine methods and cues that web developers, scientific writers, and graphic designers currently use to restore mental context. We find that participants from all three professions engage in situated sensemaking, reconstructing context by generating stories to explain cues in their documents with implicit meaning, such as sudden changes in writing quality or the shape of blocks of code. We identify characteristics of each activity that influence the information, artifacts, and strategies participants used to reconstruct context. We conclude that visual histories can help users reconstruct mental context but that challenges remain in designing lightweight image-based cues that help users reconstruct context for a range of activities.